EMCAPA: technical solutions for sustainable development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The Enterprise for Farm Research (EMCAPA) is a mixed capital company under private ownership and is linked to the State Secretariat of Rural Development and Agriculture in the Brazilian state of Espirito Santo. Since its creation in 1973, it has...